Understanding Immune Thrombocytopenia: Looking Out of the Box - Schifferli, Alexandra; Cavalli, Franco; Godeau, Bertrand; Liebman, Howard A.; Recher, Mike; Imbach, Paul; Kühne, Thomas (Frontiers in Medicine, 2021)
The pathogenesis of immune thrombocytopenia (ITP) is increasingly being elucidated, and its etiology is becoming more frequently identified, leading to a diagnostic shift from primary to secondary ITP. The overlap between autoimmunity, immunodeficiency, and cancer is evident, implying more interdisciplinarity in daily care. This mini-review is based on an expert meeting on ITP organized by the Intercontinental Cooperative ITP Study Group and presents the challenges of hematologists in elucidating and investigating “out of the box” concepts associated with ITP.